2008
DOI: 10.2466/pms.107.1.99-113
|View full text |Cite
|
Sign up to set email alerts
|

Second and Foreign Language Listening: Unraveling the Construct

Abstract: Identifying the variables which contribute to second and foreign language (L2) listening ability can provide a better understanding of the listening construct. This study explored the degree to which first language (L1) listening ability, L2 proficiency, motivation and metacognition contribute to L2 listening comprehension. 115 Persian-speaking English as a Foreign Language (EFL) university students completed a motivation questionnaire, the Language Learning Motivation Orientation Scale, a listening questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…On the opposite side of the affective domain, there is a motivation factor which contributes to language learning in the reverse direction. Motivation has been reported to yield a moderate correlation with L2 listening comprehension (Tafaghodtari & Vandergrift, 2008).…”
Section: Affective Componentsmentioning
confidence: 99%
“…On the opposite side of the affective domain, there is a motivation factor which contributes to language learning in the reverse direction. Motivation has been reported to yield a moderate correlation with L2 listening comprehension (Tafaghodtari & Vandergrift, 2008).…”
Section: Affective Componentsmentioning
confidence: 99%
“…The development of metacognitive awareness of listening was gauged with the Metacognitive Awareness Listening Questionnaire (MALQ), which was rigorously developed and validated in Vandergrift,Goh,Mareschal,andTafaghodtari(2006).Thequestionnaireconsistsof21itemswith fivefactors:Planning-evaluation,DirectedAttention(strategiestoconcentrateandstayontask),Person Knowledge(perceptionsoflisteningdifficulty,self-efficacy,listeninganxiety),MentalTranslation (thetranslationstrategieslearnersshouldavoidduringlistening),andProblem-solving(aclusterof strategiestosolvecomprehensionproblemsandtomake/monitorinferences).AccordingtoVandergrift etal. ( 2006),metacognitiveawarenessofthefivefactorsisoptimaltocorrelatesignificantlywithL2 learners'listeningperformance.Previousresearchers (Vandergrift,Goh,Mareschal&Tafaghodtari, 2006;Tafaghodtari & Vandergrift, 2008;Vandergrift & Baker, 2015;Satori, 2021) found that metacognitiveawarenessmeasuredwiththisquestionnairecansignificantlypredict3-22%variances ofL2listeningcomprehensionsuccess.Sofar,manymetacognitivelisteninginstructionstudies(e.g. Bozorgian, 2014;Bozorgian & Alamdari, 2018;Mahdavi & Miri, 2017;Rahimi & Katal, 2013;Vandergrift&Tafaghodtari,2010)haveemployedtheMALQandprovedtheinternalconsistency reliabilityofMALQtobeatanacceptablelevel(thecoefficientα>0.7).However,sinceL2learners mightmisinterpretthedescriptionsofitemsinthequestionnaire (Vandergrift&Tafaghodtari,2010), werephrasedtheseitems(e.g."ItranslatekeywordsasIlisten.…”
Section: Instrumentmentioning
confidence: 70%
“…Phonological knowledge enables L2 listeners to recognize and manipulate syllables and segment phonemes; grammatical and syntactic knowledge enable listeners to decode and convert words to a combined meaning; and pragmatic knowledge enables listeners to infer the implied meaning of the message (Lynch, 2010). These elements of linguistic knowledge should be an integral part of any model of listening (Tafaghodtari & Vandergrift, 2008). Our two-layered model can be said to consist of a continuum of lower-order and higher-order listening abilities, and the subskill groups can help distinguish between comprehension success and failure of listeners, that is, they can be operationalized for L2 listening diagnostic purposes (Y.-W. Lee & Sawaki, 2009;Lynch & Mendelsohn, 2013).…”
Section: Operationalized Definitionsmentioning
confidence: 99%